Strontium ranelate: in search for the mechanism of action - Stepan, Jan J (Journal of bone and mineral metabolism, 2013)
Strontium ranelate is a medicine with evidenced effects on the risk of fractures. The heterogeneity of strontium distribution in bone, quality of bone mineral crystals in young bone packets on bone surfaces formed during strontium ranelate administration, and activation of the calcium sensing receptor may, at least partially, explain the beneficial effects of SrR on reducing the risk of fractures. In this review, the concept of the dual action of strontium ranelate is also discussed. However, sufficient evidence for the bone anabolic effect of SrR does not exist in humans. The knowledge of the mechanism of action of SrR is important not only for the explanation of the effects of SrR upon the skeleton, but also for the safety of treatment for other tissues.
Keywords: Bone and Bones; thiofeny; Animals; kosti a kostní tkáň; zvířata; Humans; Thiophenes; Fractures, Bone; fraktury kostí; Bone Density; lidé; kostní denzita